High Rate Navigation, State Parameter, and Microphysics Flight-Level Data [NCAR/EOL] - UCAR/NCAR - Earth Observing Laboratory (Arctic Data Center)
This data set includes airborne measurements obtained from the NSF/NCAR C-130 aircraft (Tail Number: N130AR) during the Beaufort Arctic Storms Experiment (BASE). This dataset contains high rate navigation, state parameter, and microphysics flight-level data in NetCDF format.